Nanoparticles Decorated on Resin Particles and Their Flame Retardancy Behavior for Polymer Composites. (19th July 2017) - Attia, Nour F.; Zayed, Mohamed
Abstract : New nanocomposites have been developed by doping of amberlite IR120 resin with spherical TiO2 nanoparticles in the presence of maleate diphosphate. Polystyrene composites of resin, maleate diphosphate, and resin-maleate diphosphate were prepared individually. This is in addition to preparation of polymer nanocomposites of polystyrene-resin doped TiO2 nanoparticles-maleate diphosphate. The flame retardancy and thermal stability properties of these developed polymer composites were evaluated. The inclusion of resin and resin doped nanoparticles improved the fire retardant behavior of polystyrene composites and enhanced their thermal stability. Synergistic behavior between flame retardant, resin, and nanoparticles was detected. The rate of burning of the polymer nanocomposites was recorded as 10.7 mm/min achieving 77% reduction compared to pure polystyrene (46.5 mm/min). The peak heat release rate (PHRR) of the new polymer composites has reduced achieving 46% reduction compared to blank polymer. The morphology and dispersion of nanoparticles on resin and in polymer nanocomposites were characterized using transmission and scanning electron microscopy, respectively. The flame retardancy and thermal properties were evaluated using UL94 flame chamber, cone tests, and thermogravimetric analysis, respectively.